Single-Chamber Leadless Cardiac Pacemaker in Patients Without Atrial Fibrillation: Findings From Campania Leadless Registry - Russo, Vincenzo; D'Andrea, Antonello; De Vivo, Stefano; Rago, Anna; Manzo, Gianluca; Bocchetti, Antonio; Papa, Andrea Antonio; Giordano, Valerio; Ammendola, Ernesto; Sarubbi, Berardo; Golino, Paolo; D'Onofrio, Antonio; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Little is known about the clinical performance of single-chamber leadless pacemaker (LLPM) in patients without atrial fibrillation (AF) as pacing indication. The aim of this study was to describe the clinical characteristics of patients who underwent single chamber LLPM implantation at three tertiary referral centers and to compare the safety and effectiveness of the single-chamber LLPM among patients with or without AF. Materials and Methods: All the consecutive patients who underwent LLPM implantation at three referral centers were analyzed. The indications to LLPM in a real-world setting were described. The study population was divided into two groups according to AF as pacing indication. We assessed the procedure-related complications; moreover, we compared syncope, cardiac hospitalization, pacemaker syndrome, and all-cause death recurrence during the follow-up between patients with and without AF as pacing indication. Results: A total of 140 consecutive patients (mean age, 76.7 ± 11.24 years, men 64.3%) were included in the study. The indication to implantation of LLPM was permanent AF with slow ventricular response (n: 67; 47.8%), sinus node dysfunction (n: 25; 17.8%), third atrioventricular block (AVB) (n: 20; 14.2%), second-degree AVB (n: 18; 12.8%), and first degree AVB (n: 10; 7.1%). A total of 7 patients (5%) experienced perioperative complications with no differences between the AF vs. non-AF groups. During a mean follow-up of 606.5 ± 265.9 days, 10 patients (7.7%) died and 7 patients (5.4%) were reported for cardiac hospitalization; 5 patients (3.8%) experienced syncope; no patients showed pacemaker syndrome. No significant differences in the clinical events between the groups were shown. The Kaplan–Meier analysis for the combined endpoints did not show significant differences between the AF and non-AF groups [hazard ratio (HR): 0.94, 95% CI: 0.41–2.16; p = 0.88]. Conclusion: Our real-world data suggest that LLPM may be considered a safe and reasonable treatment in patients without AF in need of pacing. Further studies are needed to confirm these preliminary results.